2017
DOI: 10.3390/biology6010004
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Oxidant Defense System of the Marine Polar Ciliate Euplotes nobilii: Characterization of the MsrB Gene Family

Abstract: Organisms living in polar waters must cope with an extremely stressful environment dominated by freezing temperatures, high oxygen concentrations and UV radiation. To shed light on the genetic mechanisms on which the polar marine ciliate, Euplotes nobilii, relies to effectively cope with the oxidative stress, attention was focused on methionine sulfoxide reductases which repair proteins with oxidized methionines. A family of four structurally distinct MsrB genes, encoding enzymes specific for the reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Virtually all eukaryotic cells contain Cu,Zn SODs [37][38][39][40][41][42], as well as other anti-stress proteins that allow species to withstand environmental stresses of both natural and anthropogenic origin [43][44][45][46][47][48][49][50][51][52][53]. Our results indicated that a gene coding for cytosolic Cu,Zn SOD is present in the genome of the Antarctic icefish C. hamatus and is expressed as active protein in various organs.…”
Section: Discussionmentioning
confidence: 86%
“…Virtually all eukaryotic cells contain Cu,Zn SODs [37][38][39][40][41][42], as well as other anti-stress proteins that allow species to withstand environmental stresses of both natural and anthropogenic origin [43][44][45][46][47][48][49][50][51][52][53]. Our results indicated that a gene coding for cytosolic Cu,Zn SOD is present in the genome of the Antarctic icefish C. hamatus and is expressed as active protein in various organs.…”
Section: Discussionmentioning
confidence: 86%
“…Increased ROS formation 1 , increased DNA damage 9 , antioxidant defense inhibition 10 [196] Homo sapiens PFOA, PFOS Estrogenicity and anti-estrogenicity 12 [202] Homo sapiens PFOA, PFOS, PFNA Estradiol production 13 , progesterone 13 production, testosterone production 13 [203] Homo sapiens PFOA, PFOS Thyroid diseases [213] Homo sapiens PFOA, PFOS Chronic kidney diseases [216] Homo sapiens PFHxS, PFOA, PFOS, PFNA Decreased eGFR 14 [217] Homo sapiens PFHxs, PFOA, PFOS Increased cholesterol outcomes 15 [218] Homo sapiens PFOA, PFOS, PFNA Hyperglycemia 16 , increased serum HDL cholesterol 16 , increased blood insulin 17 [219] Homo sapiens PFOA, PFOS Increased blood levels of glucocorticoid 17 , increased blood levels of androgenic hormones 18 [222]…”
Section: Pfas Effects Referencesmentioning
confidence: 99%
“…All living organisms respond to a high presence of ROS by increasing the expression of antioxidant enzymes and many other molecules that are elements of the defense and repair toward oxidative damage [10]. Enzymatic antioxidants include proteins such as superoxide dismutase (SOD) [11,12], catalase (CAT) [13], glutathione peroxidase (GPx) [14], peroxiredoxins (Prdx) [15,16], and methionine sulfoxide reductases (Msr) [17]. These enzymes represent a first line against ROS, but do not guarantee complete coverage from the risk of oxidative stress because some compounds, generated by their reactions, are still reactive and potentially cytotoxic, such as the hydrogen peroxide (H 2 O 2 ) produced by SOD.…”
Section: Introductionmentioning
confidence: 99%
“…The production of ROS in plants, algae and microorganisms is induced by a variety of environmental stressors, such as heat, salinity, drought, high light, heavy metals and UV radiation 20,[32][33][34][35][36] . Consequently, plant, protozoa and microbial cells use their antioxidant defense mechanisms to tackle ROS formation threats through enhancing their enzymatic and non-enzymatic antioxidant systems 32,[37][38][39][40] .…”
Section: Discussionmentioning
confidence: 99%